Increased postoperative myeloperoxidase concentration associated with low baseline antioxidant capacity as the risk factor of delirium after cardiac surgery. (31st December 2022) - Kaźmierski, Jakub; Miler, Piotr; Pawlak, Agnieszka; Jerczyńska, Hanna; Nowakowska, Karina; Walkiewicz, Grzegorz; Woźniak, Katarzyna; Krejca, Michał; Wilczyński, Mirosław
Abstract: Background: Though risk factors of postoperative delirium are well described, its pathophysiology is still undiscovered. The primary objective of the current study is to assess whether increased pre- and postoperative myeloperoxidase (MPO) levels are associated with postoperative delirium in the population of cardiac surgery patients. The secondary objective is to evaluate the correlation between MPO levels and serum antioxidant capacity (AC). Methods: The patients' cognitive status was assessed one day preoperatively with the use of the Mini-Mental State Examination Test and the Clock Drawing Test. A diagnosis of major depressive disorder and anxiety disorders was established based on DSM-5 criteria. Blood samples for MPO and AC levels were collected both pre- and postoperatively. The Confusion Assessment Method for the Intensive Care Unit was used to screen for a diagnosis of delirium. Results: Delirium occurred in 34% (61 of 177) of patients. Multivariable logistic regression analysis revealed that increased postoperative MPO concentration was independently associated with postoperative delirium development, and negatively correlated with lower baseline serum AC. Conclusions: Cardiac surgery patients with less efficient antioxidative mechanisms experience a higher postoperative peak of serum MPO, which in turn may predispose to postoperative delirium development. KEY MESSAGES: MPO is a lysosomal enzyme with strong pro-oxidative and pro-inflammatory properties. Cardiac surgery patients who have increased concentration of postoperative MPO are at significantly higher risk of postoperative delirium development. This higher level of postoperative MPO is negatively correlated with baseline antioxidant capacity (AC). It can be hypothesized that individuals with decreased baseline AC experience a higher peak of MPO post-surgery due to less efficient antioxidative mechanisms, which in turn contributes to postoperative delirium development.